Fish in the matrix: motor learning in a virtual world - Engert, Florian (Frontiers in Neural Circuits, 2013)
One of the large remaining challenges in the field of zebrafish neuroscience is the establishment of techniques and preparations that permit the recording and perturbation of neural activity in animals that can interact meaningfully with the environment. Since it is very difficult to do this in freely behaving zebrafish, I describe here two alternative approaches that meet this goal via tethered preparations. The first uses head-fixation in agarose in combination with online imaging and analysis of tail-motion. In the second method, paralyzed fish are suspended with suction pipettes in mid-water and nerve root recordings serve as indicators for intended locomotion. In both cases fish can be immersed into a virtual environment and allowed to interact with this virtual world via real or fictive tail motions. The specific examples given in this review focus primarily on the role of visual feedback– but the general principles certainly extend to other modalities, including proprioception, hearing, balance and somatosensation.